Measurement of equivalence using a patient-reported daily pain diary across three smartphone devices - Conrad, Elisa; Gary, Sarah; Khurana, Laura; Otero, Tony; Ly, Jenny; Dallabrida, Susan (International Journal of Clinical Trials, 2019)
Background: Patient-reported outcomes play an essential role in evaluating the results of clinical trials. As technological advances are made throughout the industry, pharmaceutical sponsors’ ability to collect field-based patient data has greatly increased. Recently, many clinical trials are utilizing varying modes of data capture in order to enable maximum flexibility. Given the regulatory concern over the equivalence of mixed modes of administration, the need to research the use of varying devices is essential. Methods: This study reviewed three handheld smartphone devices for conceptual equivalence and conducted usability for standard questions used in a daily pain diary. Ten participants, 7 females 3 males; ages 27-70 years, diagnosed with chronic pain or fibromyalgia, completed the same pain diary on three different smartphone devices. Results: Overall, participants reported no differences between these three smartphone devices and found the presentation of the diary content to be similar, if not identical, on all three devices. Conclusions: Device type had no impact on the presentation of the diary content or participants’ understanding of the diary questions.